Tanggungjawab Hukum Institusi Rehabilitasi Medis Bagi Penyalahguna Narkoba - Wahyudi; Mohamad Riyad Mintarja; Nuryamin; Diana Farid; Muhammad Husni Abdulah Pakarti; Ais Surasa (al-Battar: Jurnal Pamungkas Hukum, 2024)
This research aims to measure the effectiveness of medical rehabilitation services provided by mandatory reporting institutions. Medical rehabilitation for drug addicts and substance abusers is a comprehensive effort aimed at freeing individuals involved in drug abuse from addiction. This rehabilitation can be carried out in healthcare facilities recognized and selected by the Ministry of Health, including Government and private healthcare facilities in collaboration with the government in providing drug rehabilitation services. Medical rehabilitation services play a crucial role in helping individuals who have committed legal violations reintegrate into society. This study adopts a qualitative research approach by implementing in-depth interviews with medical staff, rehabilitation participants, and institution supervisors. The research findings indicate that the effectiveness of medical rehabilitation services is significantly influenced by factors such as the competence of medical staff, the organized rehabilitation programs, support from various relevant parties, and hindering factors. The provision of medical rehabilitation services for drug addicts and substance abusers is regulated by the Minister of Health Regulation Number 4 of 2020 concerning the Implementation of Mandatory Reporting Institution, where Standard Operating Procedures have been well-established and defined to operate efficiently and optimally of medical rehabilitation services provided by Mandatory Reporting Institutions.